5ln(x+9)-4lnx=

Simple and best practice solution for 5ln(x+9)-4lnx= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5ln(x+9)-4lnx= equation:


Simplifying
5ln(x + 9) + -4lnx = 0

Reorder the terms:
5ln(9 + x) + -4lnx = 0
(9 * 5ln + x * 5ln) + -4lnx = 0
(45ln + 5lnx) + -4lnx = 0

Combine like terms: 5lnx + -4lnx = 1lnx
45ln + 1lnx = 0

Solving
45ln + 1lnx = 0

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(45 + x) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(45 + x)' equal to zero and attempt to solve: Simplifying 45 + x = 0 Solving 45 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '-45' to each side of the equation. 45 + -45 + x = 0 + -45 Combine like terms: 45 + -45 = 0 0 + x = 0 + -45 x = 0 + -45 Combine like terms: 0 + -45 = -45 x = -45 Add '-1x' to each side of the equation. x + -1x = -45 + -1x Combine like terms: x + -1x = 0 0 = -45 + -1x Simplifying 0 = -45 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 1.8x+9=5.7x-6 | | 3T-2=5T+6 | | 2=0.14285714285(4)+c | | 5x-2x+x=15 | | 3x^2-5x-1=2 | | 4a*2+12ab+96*2= | | y^2-3y+10=0 | | 16-7x=-4-3x | | -9-9x=-18-18x | | 49x=20x+2030 | | 2+6x=72 | | 187=l*11 | | -4(t-4+8t)=6t-8 | | x^3-4x^2-49x=-196 | | (5rq^3)(-3r^4q)=0 | | x-2=-5X-1 | | 5c^3+15c^2-270c=0 | | -x^2+12x=-3 | | 2n-3=3n+2 | | 3x+1-4x+8=3x-4x+6 | | 6x+4=-24+x | | -4x-8=-16-8x | | 7+2x=-5x-14 | | 5x-9=10x-59 | | 3x/2-7=x/4-2 | | 9x+9=-x+39 | | 50.2+.02= | | 7x^2+22x+3=3 | | 7x-(3y+8x)= | | 0=-2(4+3v)-8(-8v-1) | | 7U-14=3U+14 | | x+4=-4+9 |

Equations solver categories